1974
DOI: 10.1111/j.1528-1157.1974.tb04034.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Age‐Dependent Biochemical Changes in Mice Susceptible to Seizures

Abstract: Summary Mice susceptible to audiogenic seizures (DBA strain) and mice not susceptible (C57 strain) were tested by elevating the body temperature. At 30 days of age 64% of the DBA mice developed convulsions and one‐quarter died, whereas only 1 of 20 of the C57 mice had a convulsion although one‐fifth died. At 20 days 15% of DBA mice had a convulsion, at 40 days none did. Mice of the DBA strain thus seem to be a valid animal model of febrile convulsions in humans. At the age of peak susceptibility to convulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Investigators comparing induction of two different kindling models within the same animal have usually noted that one type of seizure kindling increases vulnerability to another type of kindling (Cain, 1980(Cain, , 1981(Cain, , 1983Holmes and Weber, 1983), although occasional exceptions are noted (Okada et al, 1985; Thompson et al, 1988). Genetic models have almost unanimously demonstrated an increased vulnerability to other types of seizure inducement (Hamburgh and Vicari, 1960;Hertz et al, 1974;Deckard et al, 1976;Wada et al, 1976;Zhao et al, 1985;Savage et al, 1986;Sugaya et al, 1986). A single contradictory study comparing susceptibility to audiogenic seizures and vulnerability to hyperthermia-induced seizures in mice showed no cross-strain correlation between them, suggesting that separate genetic factors contribute to development of each of these features (Maxson, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators comparing induction of two different kindling models within the same animal have usually noted that one type of seizure kindling increases vulnerability to another type of kindling (Cain, 1980(Cain, , 1981(Cain, , 1983Holmes and Weber, 1983), although occasional exceptions are noted (Okada et al, 1985; Thompson et al, 1988). Genetic models have almost unanimously demonstrated an increased vulnerability to other types of seizure inducement (Hamburgh and Vicari, 1960;Hertz et al, 1974;Deckard et al, 1976;Wada et al, 1976;Zhao et al, 1985;Savage et al, 1986;Sugaya et al, 1986). A single contradictory study comparing susceptibility to audiogenic seizures and vulnerability to hyperthermia-induced seizures in mice showed no cross-strain correlation between them, suggesting that separate genetic factors contribute to development of each of these features (Maxson, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…However, in brain slices of DBA/2 mice at 30 days of age, the K + -stimulated release of GABA is considerably lower than that of C57 mice [35]. Furthermore, the number of GABA receptor binding sites is reduced in the brain of DBA/2 mice, while the affinities of these sites are higher than that in control mice of comparable age [59].…”
Section: Dba/2 Mice and Gabamentioning
confidence: 94%
“…Microsomal Na + /K + ATPase activity in DBA/2 mice was reported to be depressed (vs C57) with a resulting decrease in intracellular K + concentration at the peak age of seizure susceptibility [35]; however, subsequent studies have failed to confirm this result [36]. The main neurotransmitter systems (i.e., GABA, excitatory amino acids, catecholamine, and serotonin) in the brain of DBA/2 mice have been the object of many studies.…”
Section: The Dba/2 Mousementioning
confidence: 97%
“…Moreover, other age-related biochemical changes have also been demonstrated. For example, Hertz, Schousboe, Formby, and Lennox-Buchthal (1974) reported that at the age of peak AGS susceptibility DBA/2J mice had marked diminution in sodium-potassium-activated adenosine triphosphatase, diminished potassium, diminished potassium-stimulated release of gamma amino butyric acid, and diminished oxygen uptake.…”
Section: Discussionmentioning
confidence: 99%